Prevalence of Brain MRI Markers of Hemorrhagic Risk in Patients with Stroke and Atrial Fibrillation - Karayiannis, Christopher; Soufan, Cathy; Chandra, Ronil V.; Phan, Thanh G.; Wong, Kitty; Singhal, Shaloo; Slater, Lee-Anne; Ly, John; Moran, Chris; Srikanth, Velandai (Frontiers in Neurology, 2016)
Background and Purpose: Cerebral microbleeds, cortical superficial siderosis, white matter lesions and cerebral atrophy may signify greater bleeding risk particularly in patients in whom anticoagulation is to be considered. We investigated their prevalence and associations with stroke type in patients with stroke and atrial fibrillation. Material and Methods: Cross-sectional sample, Monash Medical Centre (Melbourne, Australia) between 2010 and 2013, with brain MRI. MRI abnormalities were rated using standardized methods. Logistic regression was used to study associations adjusting for age and sex. Results: There were 170 patients, mean age 78 years (SD 9.8), 154 (90.6%) with ischemic stroke. Prevalence of MRI markers were: any microbleed 49%, multiple (≥2) microbleeds 30%, confluent white matter lesions 18.8%, siderosis 8.9%, severe cerebral atrophy 37.7%. Combinations of the severe manifestations of these markers were much less prevalent (2.9% to 12.4%). Compared with ischemic stroke, those with hemorrhagic stroke were more likely to have ≥10 microbleeds (OR 5.50 95% CI 1.46-20.77, p=0.012) and siderosis (OR 6.24, 95% CI 1.74-22.40, p=0.005). Siderosis was associated with multiple microbleeds (OR 8.14, 95% CI 2.38 - 27.86, p = 0.001). Patients admitted with hemorrhagic stroke and multiple microbleeds were more frequently anticoagulated prior to stroke (6/7, 85.7%) than in those with single (1/2, 50%) or no microbleeds (4/7, 57%). Conclusion: Multiple CMBs, severe WML, and severe cerebral atrophy were common individually in hospitalized patients with stroke and AF, but less so in combination. A higher burden of CMBs may be associated with ICH in stroke patients with AF.